Uneven Land Subsidence Patterns Along Java's Northern Urban Corridor (Pantura Route) from 2.5D SBAS InSAR Approach - Janur, Afif; Harintaka, Harintaka; Suhadha, Argo Galih (Indonesian Journal on Geoscience, 2025)
Land subsidence is a phenomenon that occurs in many parts of the world, particularly in coastal plains and river delta areas, including the north coast of Java, commonly known as ‘pantura’. By utilizing satellite time series data, land subsidence along the north coast of Java was detected using The Small Baseline Subset (SBAS) method. Additionally, combining data from different Sentinel-1 orbit directions (ascending-descending) enables the production of a more accurate 2.5D model. This research aims to calculate the rate of land subsidence on the north coast of Java from 2020 to 2023 using the 2.5D model, and to compare the results with CORS processing results. Recent identification of land subsidence highlights that residential areas and rice fields are highly vulnerable to potential subsidence. The 2.5D model in the up-down (UD) direction shows the highest land subsidence occurred in Demak Regency at 146.45 mm/year, Semarang City at 144.34 mm/year, and Pekalongan Regency at 137.94 mm/year. An accuracy assessment was performed using twelve CORS stations, showing RMSE values ranging from millimeters to centimeters: vertical ascending at 16.5 mm, vertical descending at 18.6 mm, UD at 8.8 mm, and East ̶ West (EW) at 26.3 mm.